Early and chronic gray matter volume changes in limbic encephalitis revealed by voxel‐based morphometry. (23rd March 2015) - Wagner, Jan; Weber, Bernd; Elger, Christian E.
Summary Objective Antibody‐associated limbic encephalitis (LE) is an increasingly recognized cause of mostly adult‐onset temporal lobe epilepsy. Magnetic resonance imaging (MRI) typically shows volume and signal changes of the mesiotemporal structures. However, recent studies indicate that imaging characteristics depend on the type of the associated antibody. The aim of the present study was to investigate early and chronic gray matter (GM) volume changes in LE by means of voxel‐based morphometry (VBM). Methods Optimized VBM analysis was applied to altogether 73 MRI volumes of 55 patients with antibody‐associated LE. Based on the time point of MRI acquisition, patients were split into two separate groups to enable the evaluation of early (≤2 years after LE onset) and chronic (>2 years after LE onset) GM volume changes. In addition, separate analyses for the two most common LE subtypes in our study cohort, that is, glutamic acid decarboxylase (GAD)–associated LE and voltage‐gated potassium channel (VGKC)‐complex–associated LE were performed. Age‐ and gender‐matched healthy subjects served as controls. Results Referring to the entire LE group, VBM revealed bi‐amygdalar GM volume increase in the early disease stage. In the chronic disease stage, amygdala enlargement had resolved and we found GM volume reduction in the right cerebellar hemisphere. In the subgroup analysis, VBM showed corresponding bi‐amygdalar GM volume increase in VGKC‐complex–associated LE on early MRI, whereas no changes were found in GAD‐associated LE. In the chronic disease stage, VBM revealed left frontal GM volume increase in VGKC‐complex–associated LE and right frontoparietal GM volume reduction in GAD‐associated LE. Significance The present study provides further evidence of a predominant affection of the amygdala in the early disease stage of LE, which resolves during the later course of the disease. Furthermore, our results show that LE features distinct imaging characteristics depending on the associated antibody and thus may contribute to a better pathophysiologic understanding of this disease.